Harnessing Dendritic Cell Function in Hepatocellular Carcinoma: Advances in Immunotherapy and Therapeutic Strategies - Shiding Ying; Haiyan Liu; Yongliang Zhang; Yu Mei (Vaccines)
Hepatocellular carcinoma (HCC) is a major cause of cancer-related mortality worldwide. Conventional therapies are frequently limited by tumor heterogeneity and the immunosuppressive tumor microenvironment (TME). Dendritic cells (DCs), central to orchestrating antitumor immunity, have become key targets for HCC immunotherapy. This review examines the biological functions of DC subsets (cDC1, cDC2, pDC, and moDC) and their roles in initiating and modulating immune responses against HCC. We detail the mechanisms underlying DC impairment within the TME, including suppression by regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), and cancer-associated fibroblasts (CAFs). Additionally, we discuss novel DC-based therapeutic strategies, such as DC-based vaccines designed to enhance antigen presentation and T cell activation. Combining DC vaccines with immune checkpoint inhibitors (ICIs), including PD-1/PD-L1 and CTLA-4 blockers, demonstrates synergistic effects that can overcome immune evasion and improve clinical outcomes. Despite progress, challenges related to DC subset heterogeneity, TME complexity, and patient variability require the further optimization and personalization of DC-based therapies. Future research should focus on refining these strategies, leveraging advanced technologies like genomic profiling and artificial intelligence, to maximize therapeutic efficacy and revolutionize HCC treatment. By restoring DC function and reprogramming the TME, DC-based immunotherapy holds immense potential to transform the management of HCC and improve patient survival.